Knowledge, Attitude and Use of Contraceptives Among Women of Reproductive Age in a Nigerian Rural Community: Evaluation of Contraceptive Utilization Among Rural Women - Gbuchie, Monica Anurika; Enughwure, Ese Edirin; Daniel, Faithful Miebaka; Obosi, Buokuromu Churson; Ezinne Emeruwa, Victoria (International Journal of Medical Students, 2023)
BACKGROUND: The use of contraception, encompassing various methods such as hormonal pills, condoms, intrauterine devices, and natural techniques like abstinence, plays a pivotal role in family planning and reproductive health. Despite its importance, the utilization of contraceptives, particularly in low-resource nations like Nigeria, has remained notably low. This is concerning, considering the positive impact of contraception on maternal and child health and its contribution to national development by curbing population growth. In Nigeria, awareness of contraception is relatively high, but the adoption of modern contraceptive methods is alarmingly low, with only 10% of females utilizing them. This rate is notably insufficient given the high levels of sexual activity, especially among adolescents and young adults. Furthermore, regional disparities exist within Nigeria, with the south-south geopolitical zone exhibiting a higher prevalence of modern contraceptive use at 15.5%. Factors influencing contraceptive usage include education, religious beliefs, and awareness of available methods. In Yenagoa, Bayelsa state, the prevalence of modern contraceptives was notably higher at 36.8% in 2017, underscoring the impact of education and knowledge of contraceptive options. Increasing contraceptive use is crucial for Nigeria, a lower-middle-income country, as it not only aids in averting unplanned pregnancies and maternal mortality but also in controlling population growth. AIM: The study aimed to shed light on contraceptives' profound health advantages to both women and families. By investigating the knowledge, attitude, and use of contraceptives within the context of the study community, it sought to contribute to the promotion and enhancement of contraceptive use among women of reproductive age in the rural community of Sagbama, South-south Nigeria. METHODS: A descriptive cross-sectional study was conducted among women of reproductive age, over a period of 3 months in Sagbama Community, Bayelsa state. Multi-stage sampling was employed. Data was obtained using interviewer-administered semi-structured 31-item questionnaire and analyzed using IBM SPSS version 26. Bivariate analysis with p-value <0.05 was significant. RESULTS: Among the 314 respondents, the mean age was 29.96 years. Nearly half were married (48.4%), with varying numbers of children. The majority had some form of education, with 46.8% having secondary education. Most respondents (95.9%) had heard of contraceptives, primarily from friends (76.4%) and hospitals (58%). The most well-known contraceptive methods were male condoms (95.9%), contraceptive pills (79.9%), and implants (72.3%). Positive attitudes toward contraceptive use were observed in 83.4% of respondents, driven by the desire to prevent unwanted pregnancies and space births (80.9%). Of sexually active women (81.4%), 53.3% used contraceptives, with male condoms (44%) and pills (15.7%) being the most common methods. Reasons for non-use included a perceived lack of need (28.6%) and fear of side effects (26.5%). CONCLUSION: Despite high knowledge levels, the use of contraceptives among women of reproductive age in the community was poor. Education and addressing misconceptions are essential to promote effective contraceptive use. Comprehensive health and sex education involving both men and women should be provided to dispel misconceptions and encourage correct contraceptive use.